Knowledge Management and Business Performance: Global Experts’ Views on Future Research Needs - Perez-Arrau, J (Emerald Group Publishing Ltd., 2016)
Purpose: This paper aims to examine the views of the global knowledge management (KM) community on the research area of KM and business performance and identify key future research themes. Design/methodology/approach: An interview study spanning 222 informants in 38 countries was launched to collect data on KM expert views concerning the future research needs of the KM field. Findings: The value contribution of KM requires more research despite experts agreeing on the complexities involved in solving this challenge. Further research areas identified were related to the influence of KM to support business strategy, intellectual capital, decision-making, knowledge sharing, organizational learning, innovation performance, productivity and competitive advantage. Research limitations/implications: The sample is dominated by European-based KM experts and the self-selecting sampling approach that was used by relying on the networks of each partner could have biased the structure of this sample. Practical implications: The recognition of the complexity to demonstrate the value contribution of KM could prevent practitioners from using over-simplified approaches and encourage them to use more advanced measurement approaches. Originality/value: The paper is unique, in that it reports on the views of 222 KM experts from 38 countries representing both academia and practice, on the issue of future research needs in terms of KM and business outcomes. As such it provides valuable guidance for future studies in the KM field and related subjects. © 2016, © Emerald Group Publishing Limited.